Problematising problematisation: insights from critical pedagogy in a writing lesson in Bangladesh - Talukder, Ali Azgor; Samuel, Moses (Taylor & Francis, 2018)
Problematisation is the means by which critical pedagogy attempts to destabilise power relations related to gender, race, class, identity etc. Studies in critical pedagogy in language teaching explore different ways of problematisation treating problematisation as classroom practice. However, they do not specifically address the teacher’s struggle in employing problematisation and the learners’ experience with it in classroom settings. Hence the complexity of problematisation remains neglected in research in critical pedagogy in classroom contexts. This article explores the notion of problematisation through an analysis of a writing lesson involving undergraduate students in Bangladesh. It analyses both the teacher’s and a student’s encounters with and reflections on problematisation throughout the lesson, and reveals that problematisation embodies complexities, and is empowering when it is self-reflexive.